Diagnostic Performance of Various Tests and Criteria Employed in Allergic Bronchopulmonary Aspergillosis: A Latent Class Analysis - Agarwal, Ritesh; Maskey, Dipesh; Aggarwal, Ashutosh Nath; Saikia, Biman; Garg, Mandeep; Gupta, Dheeraj; Chakrabarti, Arunaloke (PloS one, 2013)
The efficiency of various investigations and diagnostic criteria used in diagnosis of allergic bronchopulmonary aspergillosis (ABPA) remain unknown, primarily because of the lack of a gold standard. Latent class analysis (LCA) can provide estimates of sensitivity and specificity in absence of gold standard. Herein, we report the performance of various investigations and criteria employed in diagnosis of ABPA. Consecutive subjects with asthma underwent all the following investigations Aspergillus skin test, IgE levels (total and A.fumigatus specific), Aspergillus precipitins, eosinophil count, chest radiograph, and high-resolution computed tomography (HRCT) of the chest. We used LCA to estimate the performance of various diagnostic tests and criteria in identification of ABPA. There were 372 asthmatics with a mean age of 35.9 years. The prevalence of Aspergillus sensitization was 53.2%. The sensitivity and specificity of various tests were Aspergillus skin test positivity (94.7%, 79.7%); IgE levels>1000 IU/mL (97.1%, 37.7%); A.fumigatus specific IgE levels>0.35 kUA/L (100%, 69.3%); Aspergillus precipitins (42.7%, 97.1%); eosinophil count>1000 cells/µL (29.5%, 93.1%); chest radiographic opacities (36.1%, 92.5%); bronchiectasis (91.9%, 80.9%); and, high-attenuation mucus (39.7%, 100%). The most accurate criteria was the Patterson criteria using six components followed by the Agarwal criteria. However, there was substantial decline in accuracy of the Patterson criteria if components of the criteria were either increased or decreased from six. A.fumigatus specific IgE levels and high-attenuation mucus were found to be the most sensitive and specific test respectively in diagnosis of ABPA. The Patterson criteria remain the best diagnostic criteria however they have good veridicality only if six criteria are used.